Pressupostos teóricos e metodológicos da formação de conceitos matemáticos por educandos dos anos iniciais da EJA - Miguel, José Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Aiming at the theoretical and methodological assumptions involved in a process of formation of mathematical concepts in the first segment of adult education, the research has examined some perceptions and difficulties of students and teachers as well as pointed out alternative teaching procedures for referral of problems. Thanks to bibliographical research, performed the classroom observation and document analysis, collecting the data in a collaborative action research environment. In general, the students of EJA bring to school a vast repertoire of mathematical situations they experience on a daily basis. Informally, deal with recorded information in tables and graphs, make mental calculations with some dexterity and perform estimates that surprise to teachers. However, these skills are usually not much explored in everyday classrooms, prevailing treatment for mathematics strongly marked by algorithmic procedure that although value as procedural content contributes little to the development of logical reasoning necessary to the formation of theoretical thinking. This school conduct restricts the development of skills such as problem solving, decision making, interpret information and adapt to changes in the production process, making the integration of people in the formal labor market. The misunderstanding of the information conveyed or its purely intuitive interpretation may constitute a form of exclusion from individual citizenship. In literacy, mathematics should be treated as support to the processes of reading and writing. It is a condition to speak of effective literacy process, highlighting the complementary functions of the mathematical language and the mother tongue. The results pointed to the theoretical and practical consequences of the decision to think the teaching of mathematics as a ... (Complete abstract click electronic access below)

Tendo como objetivo os pressupostos teóricos e metodológicos envolvidos em um processo de formação de conceitos matemáticos no primeiro segmento da educação de jovens e adultos, a pesquisa procedeu à análise de algumas percepções e dificuldades de estudantes e professores bem como apontou procedimentos didáticos alternativos para encaminhamento dos problemas. Valeu-se de pesquisa bibliográfica, procedeu à observação de aulas e à análise documental, coletando-se os dados em um ambiente de pesquisa-ação colaborativa. Em geral, os educandos da EJA trazem para a escola um vasto repertório de situações matemáticas que vivenciam no dia a dia. De maneira informal, lidam com informações registradas em tabelas e gráficos, fazem cálculos mentais com alguma destreza e realizam estimativas que surpreendem aos professores. No entanto, essas habilidades geralmente não são muito exploradas no cotidiano das salas de aula, prevalecendo um tratamento para a Matemática fortemente marcado pelo procedimento algorítmico que embora tenha valor como conteúdo procedimental pouco contribui para o desenvolvimento do raciocínio lógico necessário à constituição do pensamento teórico. Essa conduta escolar restringe o desenvolvimento de habilidades como a de resolver problemas, tomar decisões, interpretar informações e adaptar-se às mudanças do processo produtivo, dificultando a inserção de pessoas no mercado formal de trabalho. A incompreensão da informação veiculada ou a sua interpretação meramente intuitiva pode se constituir em uma forma de exclusão do indivíduo do exercício da cidadania. Na alfabetização, a Matemática deve ser tratada como respaldo aos processos de leitura e de escrita. É uma ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Education; Teaching and learning; Mathematics teaching; Youth and adult education; Methodology and teaching practice; Matemática (Ensino fundamental); Ensino fundamental; Educação de adultos; Education